2010
DOI: 10.1007/s11244-010-9460-5
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Heterogeneous Catalysis for Biodiesel Synthesis

Abstract: Heterogeneous catalysts are promising for the transesterification reaction of vegetable oils to produce biodiesel and have been studied intensively over the last decade. Unlike the homogeneous catalysts, heterogeneous catalysts can be easily separated from reaction mixture and reused for many times. They are environmentally benign and could be easily operated in continuous processes. This review classifies the solid catalysts into two categories based on their catalytic temperature, i.e. high temperature catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(98 citation statements)
references
References 121 publications
2
85
0
2
Order By: Relevance
“…CaO and MgO solid based catalysts from natural resources or not, in most cases (Tables 2-4 [93] showed excellent stability as it gives good yields in transesterification and could be reused during 50 cycles in successive reactions. Yan et al [94] reported that the Zn 3 La 1 catalyst they prepared was recycled 17 times in a batch reactor without loss of activity and maintained a high FAME yield (92.3%) for 70 days in a continuous tubular flow reactor. In comparison CaO and MgO based catalysts showed a high number of reuse potentiality as above 16 uses with Ca/Ce oxide [74].…”
Section: Resultsmentioning
confidence: 99%
“…CaO and MgO solid based catalysts from natural resources or not, in most cases (Tables 2-4 [93] showed excellent stability as it gives good yields in transesterification and could be reused during 50 cycles in successive reactions. Yan et al [94] reported that the Zn 3 La 1 catalyst they prepared was recycled 17 times in a batch reactor without loss of activity and maintained a high FAME yield (92.3%) for 70 days in a continuous tubular flow reactor. In comparison CaO and MgO based catalysts showed a high number of reuse potentiality as above 16 uses with Ca/Ce oxide [74].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the use of heterogeneous solid acid catalysts to replace homogeneous ones could eliminate the problems associated with homogeneous catalysts and could enhance the use of high acid value oil to be used as feedstock for synthesis of biodiesel 6, 7 . In the last decades, various solid acids (resins, zeolite, sulfated zirconia, polyaniline sulfate, heteropolyacid, metal complexes, sulfated tin oxide, and acidic ionic liquid) have been explored as potential heterogeneous catalysts in the production of biodiesel 8, 9 . Some common problems, such as low acid site concentrations, hydrophilic character of catalyst surfaces, and active site leaching, have hampered their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The poisoning and leaching of the catalyst during the reaction led to change the physical properties as well as deactivation of the catalyst. For this reason the catalyst must be properly formulated (Yan et al, 2010). Table 2.…”
Section: Catalysts For Biodiesel Productionmentioning
confidence: 99%